Incidence of malignant mesothelioma and asbestos exposure in the Emilia-Romagna region, Italy - Mangone, Lucia; Storchi, Cinzia; Pinto, Carmine; Giorgi Rossi, Paolo; Bisceglia, Isabella; Romanelli, Antonio (La Medicina del Lavoro, 2022)
Background: The aim of this study is to describe the incidence of malignant mesothelioma (MM) and asbestos exposure in an Italian region in the period 1996-June 2021. Methods: The study included cases with microscopic confirmation and those with instrumental confirmation. For each case, information on sex, age, tumour site, morphology and date of diagnosis was collected, along with details of exposure to asbestos. Results: 3,097 cases of MM (2,233 males and 864 females) were registered: 90.8% with microscopic confirmation. A total of 2,840 cases involved the pleura (92%), 230 cases the peritoneum (7%), and a small number of cases the pericardium and testis (9 and 18, respectively). Most cases (78.0%) occurred after 65 years of age, while only 1.5% concerned individuals with age < 45 years. The standardized incidence rate for the entire period (adjusted to the 2000 Italian standard population and calculated per 100,000 person-years) was equal to 3.9 in males and 1.4 in females, and the trend showed an increase with age in both sexes. Concerning asbestos exposure, 79.7% of cases were exposed (86.7% males and 60.1% females). In 70.3%, exposure was occupational (83.4% males and 33.2% females), while 20.7% of females and 0.8% of males had familial exposure. Building construction, rolling stock manufacture/repair and metalworking were the most prevalent economic activities associated with occupational exposure. Conclusions:This study offers an overview of MM in an Italian region characterized by high incidence and high exposure due to its particular production activities.